A study of the protease inhibitory activity component of SARS-CoV-2 3CL in Bletilla striata - Yang, Yuyu; Zhang, Fei; Liu, Shihan; Jin, Wenfang; Shao, Qianshan; Li, Chunxiao; Fan, Baolei (Frontiers in Natural Products, 2024)
The protease Mpro (referred to as 3CLpro or 3CL protease) is a cysteine protease that is highly conserved in coronavirus and is indispensable for viral replication. Because there is no homologous protein for MPro in the human body, SARS-CoV-2 3CL protease is an ideal target against coronavirus. Bletilla striata (Reich. Bf.) is a well-known form of Traditional Chinese Medicine (TCM) and can exert many pharmacological effects, including hemostasis, anti-microbial and antivirus activities. Our preliminary screening showed that the n-butanol component of a methanol extract of Bletilla striata exhibited potent inhibitory activity against SARS-CoV-2 3CL protease (58.82% at 200 μg/mL). In this study, we biologically evaluated ten isolated chemical compounds from Bletilla striata and investigated the inhibitory activities of its constituents on SARS-CoV-2 3CL protease. Following bioactivity-guided fractionation, four bibenzyls (1, 4, 6 and 7), three phenols (5, 8 and 9), two anthraquinones (2 and 3) and one glucosyloxybenzyl 2-isobutylmalate (10) were isolated and evaluated for their ability to inhibit SARS-CoV-2 3CL protease by fluorescence resonance energy transfer (FRET) analysis. The binding mode between compounds and enzymes was investigated by molecular docking and Saturation Transfer Differences -nuclear magnetic resonance (STD-NMR). Moreover, Pleiobibenzynin B (7), Blestritin B, Gymconopin D (4), Physcion, 3'-Omethyl dioscin III (6), Gastrodin (8) and caffeic acid (5) all exhibited inhibitory activity against 3CL protease in vitro. The four bibenzyls (1, 4, 6 and 7) exhibited good inhibitory activity against SARS-CoV-2 3CL protease (7.37-39.86 μM). These findings identify potential new inhibitors against SARS-CoV-2 3CL protease, which offers promising lead compounds for the development of novel anti-SARS-CoV-2 drugs.